OPTIMALISASI ASET DESA DI KABUPATEN KONAWE SELATAN - Syamsul Alam; La Ode Mustafa (Universitas Halu Oleo, 2022)
This study aims to analyze the optimization of village assets in South Konawe Regency. The research method used is a qualitative method approach where data collection is carried out in a natural setting with interview, observation and documentation techniques. The data analysis technique used is a qualitative analysis of the interactive model from Miles, Huberman & Saldaña which includes data collection, data condensation, data presentation and conclusions/verification. The results of the study indicate that the optimization of village assets in Konawe Selatan Regency has not been carried out systematically as can be seen from the legal status determination of all village assets; not yet optimal use of all village assets to support governance, development, community development, and empowerment of village communities; and the utilization of village assets has not been carried out in the context of carrying out village government tasks.